Effectiveness Of Sodium Hypochlorite As A Desinfectant On Alginate Impression Materials - Stephanie Naranathadewi; Rima Parwati Sari; Kristanti Parisihni; Aprilia; Moh. Basroni Rizal (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Cross infection is a problem that has attracted attention in dentistry. One procedure that carries a risk of cross infection is impression taking. Impression is a major factor in the chain of spreading the infection because it will be contaminated with various oral microorganisms during the procedure. Impression material that is often used is alginate. Alginate has imbibition properties which increase the potential for contamination. Disinfection of alginate impression by spraying sodium hypochlorite can be a solution to prevent cross-infection effectively and efficiently. This article aims to determine the effectiveness of sodium hypochlorite as a disinfectant in alginate impressions. Review: Sodium hypochlorite will form hypochlorous acid and release active chlorine compounds. Active chlorine is a strong oxidizing agent that will inhibit bacterial enzymes and disrupt the function of cell metabolism which causes cells or bacteria to be eliminated. Conclusion: Sodium hypochlorite by spraying method has an effect on the amount of microorganism contamination of the oral cavity on the alginate impressions. Therefore sodium hypochlorite can be effectively used to disinfect the alginate impressions.